Purification and some properties of two protein proteinase inhibitors from the seeds of Sophora japonica L. f. - Quang, Le Trong; Nam, Nguyen Phuong; Ha, Phan Thi; Tran Chau, Pham Thi (Academia Journal of Biology, 2015)
Using column chromatography on superdex-75, MonoS and PAGE methods allowed to separate two highly purified protein proteinase inhibitors from Sophora japonica seeds, named SJ-I and SJ-II. Each of them showed inhibitory activity against both trypsin and chymotripsin. The molecular mass of both inhibitors were estimated around 16 kDa. However, they were different in pI value: 6.2 for SJ-I and 5.85 for SJ-II. The heat stability of two inhibitors was also similar: after the treatment of inhibitors at 70oC for 3 min, TIA remained 40% and after 15 min, TIA completely lost. All obtained data led to a suggestion that SJ-I and SJ-II were isoforms and might be a Bowman - Birk type double headed inhibitors of higher molecular mass.